Dampak Kosmopolitanisme Islam terhadap Pendidikan Islam di Dunia Global - Mahfudz Syamsul Hadi; M. Hasan Muammar (Program Pascasarjana Universitas Pesantren Tinggi Darul Ulum (Unipdu) Jombang, 2022)
Currently, Islamic Cosmopolitanism is quite diverse. Cosmopolitanism encompasses a wide range of topics, ideas, and practices that represent various interpretations and expressions of Islam. Among the varieties of Cosmopolitanism, there are those that are divisive and controversial. Here the author will analyze the potential consequences of Islamic immigration. In a global society, Cosmopolitanism is important for Islamic education. Islamic teachings are claimed to be quite interpretable to support various Islamic Cosmopolitanisms. Islamic education is always colored by change. The exchange of information and ideas democratizes and complicates Islamic hermeneutics and practice. In such an atmosphere, the author argues that the Cosmopolitan discourse of Islam has become a necessity, and that the results of this discourse will have a significant impact on Islamic education in the future. Given the historical antecedents, the author believes that if this discourse contributes to or increases polarization, the orthodoxy of Islamic education will triumph.